Carta de Horatio S. Rubens a Roberto H. Todd - Rubens, Horatio S.; Todd, Roberto H. (My University, 1929)
Carta de agradecimiento.
Keywords: Rubens, Horatio S.--Correspondence.; Rubens, Horatio S.--Correspondencia.; Todd, Roberto H.--Correspondence.; Todd, Roberto H.--Correspondencia.